O papel dos municípios mineiros no enfrentamento à mudança do clima : um diagnóstico exploratório - Rodrigues, Júlia Espeschit (2022)
Climate change has been an increasingly present topic in the agenda of governments around the world. Much has been said about the importance of the involvement of local spheres in dealing with the adverse effects of this change. However, the internalization and location of internationally agreed targets within the signatory countries are challenges to overcome. This research aims to contribute to its solution, elucidating the role of municipalities in facing the climate crisis in Brazil, specifically, in the State of Minas Gerais. To this end, the goals of the 2030 Agenda, which deals with the climate issue, and public policies, which are the responsibility of local governments (policy-decision-making instance) in Minas Gerais, were mapped, considering the intergovernmental relations of Brazilian federalism. In order to investigate the capability of municipalities from Minas Gerais to facing climate change, we selected indicators and carried out an exploratory data analysis using cluster methodology. The results suggested the formation of three groups of municipalities. According to each group performance, we can identify actions that should be adopted by municipal managements to better cope with the current climate crisis. Moreover, the results indicated that the geographical location, the size of the municipality or main economic activity do not account for the performance of municipal public management in the face of the challenges of climate change. The decision-making autonomy of municipal public management on issues relevant to facing the climate crisis puts the municipalities in a privileged position to embrace the ecological transition "without leaving anyone behind".